The ectopic spleen-incidental finding on pelvic magnetic resonance imaging - Bunyamin Güney (Medicinski fakultet Priština, Društvo lekara Kosova i Metohije Srpskog lekarskog društva, 2021)
The ectopic spleen (ES) is a rare variation occurred depend on the absence or laxity of the suspensory ligaments. The ES is a rarely diagnosed clinical condition. Less than 500 symptomatic patients have been reported. Less than 0.25% of splenectomies are performed on the ES. Patients are usually asymptomatic. It's diagnosed incidentally in general. The incidence is not clear. ES incidence is reported less than 0.5%. However, this rate covers all of the relocations. The spleen can be found anywhere in the abdomen or pelvis, depends on the length of the vascular pedicle. The pelvic ES is a rarely encountered situation. Knowing this anomaly is essential for early diagnosis and prevention serious problems such as torsion, infarction and acute abdomen. A 21 years old female patient with ES was presented on pelvic magnetic resonance imaging.